2020
DOI: 10.1002/cam4.2967
|View full text |Cite
|
Sign up to set email alerts
|

HOXD9 promote epithelial‐mesenchymal transition and metastasis in colorectal carcinoma

Abstract: Background: HOXD9, a Hox family member, is involved in cancer growth and metastasis. But, its regulation mechanism at the molecular level particularly in colorectal cancer (CRC), is mostly unknown. Methods: The HOXD9 protein expression levels were analyzed using immunofluorescence, immunohistochemistry (IHC) assays, and western blot. The in vivo and in vitro roles of HOXD9 in CRC were determined using colony formation and EdU incorporation, CCK-8, wound scratch and transwell invasion assay, and animal models. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(66 citation statements)
references
References 34 publications
3
60
0
Order By: Relevance
“…The transcription factor HOXD9 is a member of the HOX family and plays an important role in tumorigenesis. By exploring the regulatory mechanism of HOXD9 on a molecular level, HOXD9 overexpression was found to significantly enhance the migration, invasion, and metastasis of hepatoma cells, gastric cancer cells, cervical cancer cells, and CRC cells [ 26 30 ]. The TSPAN11 protein has not been thoroughly studied in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor HOXD9 is a member of the HOX family and plays an important role in tumorigenesis. By exploring the regulatory mechanism of HOXD9 on a molecular level, HOXD9 overexpression was found to significantly enhance the migration, invasion, and metastasis of hepatoma cells, gastric cancer cells, cervical cancer cells, and CRC cells [ 26 30 ]. The TSPAN11 protein has not been thoroughly studied in tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Three studies reported that patients with high HOX (B7, B9, C6) protein expression levels demonstrated signi cantly advanced T status in comparison with patients with low expression, [24,25,31], (table 1). Similarly, regarding N status, 6 studies showed that the percentage of patients with regional lymph node invasion was signi cantly increased in the high HOX expression group for the following: HOXA3, A9, B8, B9, B13, C6, D1 and D9 [21,25,30,32,41,44]. Inverse correlation between HOX expression and nodal invasion was demonstrated only for HOΧD10 by Wang et al [26](table 1).…”
Section: Findings Hox Dysregulation and Clinicopathological Signi Cance In Crcmentioning
confidence: 92%
“…Eight studies investigated the presence of metastatic disease according to HOX expression levels [24, 25, 27-30, 33, 44]. Two studies by Liao et al [31] and Huang et al [30] for HOXB7 and B9 respectively, reported that signi cantly more patients had metastatic disease in the high HOX expression group in comparison with the low expression one, ( [21,23,31,44]. For HOXB9 studies by Zhan et al [29] and Huang et al [30] reported equivocal ndings, (table 1).…”
Section: Findings Hox Dysregulation and Clinicopathological Signi Cance In Crcmentioning
confidence: 99%
“…Currently, there are some reports proposing an involvement of HOX proteins in the EMT process, with an impact on the capacity of invasion and metastasis of cancer cells [73][74][75][76]. It has been demonstrated that CDH1 expression is transcriptionally upregulated by the direct binding of HOXA5 to their promoter sequence and that the knockdown of HOXA5 in mammary cells leads to a loss of epithelial traits, increased stemness and cell plasticity, and acquisition of more aggressive phenotypes [77].…”
Section: Hox Proteins Effect In the Epithelial To Mesenchymal Transitmentioning
confidence: 99%
“…Abnormalities in these structures can lead to cell detachment from the primary tumour and enhance the potential for dissemination and metastatic spread of cancer cells to epithelial characteristics in a process called mesenchymal-to-epithelial transition (ME [72]. Currently, there are some reports proposing an involvement of HOX proteins in EMT process, with an impact on the capacity of invasion and metastasis of cancer cells [ 76]. It has been demonstrated that CDH1 expression is transcriptionally upregulated the direct binding of HOXA5 to their promoter sequence and that the knockdown HOXA5 in mammary cells leads to a loss of epithelial traits, increased stemness and plasticity, and acquisition of more aggressive phenotypes [77].…”
Section: Hox Proteins Effect In the Epithelial To Mesenchymal Transitmentioning
confidence: 99%